Effect of quantum confinement, surface states and exitonic energy levels on photoluminescence of zinc oxide nanostructures [electronic resource] - Muhammad Muhammad Nmaya, 1973- author; Sib Krishna Ghoshal, supervisor; Fakulti Sains (2014)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2014